Determinants of Health Associated with Dengue Incidence in Patients from the Lodana Health Center - Cevallos, Leonardo; Moreira, María Belén Vera; Pinargote, Mateo Juan Alcívar; Vizhñay, Matías Utria (Clinical and Research Journal in Internal Medicine, 2025)
Vector-borne diseases constitute a significant public health challenge globally, causing over 700,000 deaths annually. Among them, dengue, transmitted by Aedes mosquitoes, has emerged as a formidable threat, particularly in tropical and subtropical regions. Understanding the biology of the virus, the ecology of mosquito vectors, and the socio-economic factors influencing disease spread is imperative for effective prevention and control strategies. This multidisciplinary challenge necessitates collaboration among scientists, healthcare professionals, governments, and communities. Ecuador, experiencing a surge in dengue cases, particularly in provinces like Manabí, underscores the urgency for tailored interventions. This study aims to analyze the influence of health determinants on dengue incidence at Lodana Health Center, proposing targeted promotional strategies within the healthcare setting. The theoretical framework integrates perspectives from Health Promotion, Critical Epidemiology, and Popular Education, emphasizing community empowerment and participatory approaches to address the complexity of dengue control effectively.